EFFICIENCY OF DIFFERENTIATED LONG TERM MAINTENANCE TREATMENT IN DENTAL IMPLANT SURGERY PATIENTS - Yarov, Yu.Yu.; Silenko, Yu.I. (World of Medicine and Biology, 2018)
Purpose of this study was to evaluate the effectiveness of the proposed differential maintenance treatment in patients who underwent dental implantation, based on the results of the clinical dynamic observation and the data of laboratory tests (microbiological, immunological and rheological), depending on the initial level of the Green-Vermillion’s HI after the implant prosthetics stage, according to the clinical and radiologic control in the long-term (1 year).